The nurse’s performance in cases of cardiorespiratory arrest: an integrative literature review (Research, Society and Development, 2022)
Introduction: It is proposed to study the role of nurses in cases where the patient has cardiorespiratory arrest (CPA), because it is an emergency that requires the immediate action of nurses and that they exercise their knowledge to preserve the survival of these patients. Objectives: Discuss the process of analysis by nurses to identify the initial symptoms of a CRA; present adequate conduct for first aid actions; to identify the main post-CRA care and the nurse's action in this context. Methodology: This is a literature review carried out in the SciELO, LILASCS, Institutional Repository databases. With the application of a time frame of six years. The inclusion criteria are thematic relevance; publication time; scientific research methodologies. The exclusion criteria are empirical methodologies; articles published more than six years ago and with an escape from the proposed theme. Results: the nurse's role is essential to identify the beginning of a CRA and initiate the appropriate procedures to treat the patient, hence the importance of strict control of the patients' vital signs and also the need for a humanized care treatment. Conclusion: nursing care with patients who are on the verge of suffering a CRA, and those who have already presented the CRA condition, need to be reinforced because, with a rigid monitoring protocol and a humanized treatment, it is possible to identify the symptoms and establish a relationship of nurse-patient with quality of communication and consequently quality in preventive and repressive treatment.